Using Thermodynamic Availability to Predict the Transitional Film Reynolds Number between the Jet and Sheet Modes in Falling Liquid between Horizontal Tubes. (November 2020) - Mikhaeel, Mina M.K.; Jacobi, Anthony M.
Highlights: A widely valid model with minimal empiricism and no training on transition data. Direct prediction of the numerical values of the transitional film Reynolds numbers between the jet and sheet modes of falling films. Validation against 52 experimental data points for 10 working fluids. Model achieves a mean absolute percentage error of 20.4%, which is lower than that by the widely used Re = a ( Ga ) b model (30.4%). Abstract: The purpose of this paper is to develop and validate a theoretical framework -based on thermodynamic availability- that directly predicts the transitional film Reynolds numbers between the jet and sheet modes of falling films on horizontal tubes. The prediction of the prevailing flow mode is important for the design and operation of falling film heat and mass exchangers. The proposed model accounts for fluid properties as well as tube geometry (diameter and spacing). The transitional film Reynolds numbers calculated using the proposed model were validated against 52 experimental measurements from the literature. More than 73 % of the results from the proposed model are within  ±  25 % from their respective experimental values. Moreover, the proposed model has a mean absolute percentage error of 20.4 % which is lower than the 30.4% obtained by the widely-used empirical model ( Re = a ( Ga ) b ), for the same validation data. The proposed model offers a convenient tool for predicting the mode transitions, provides insight into the role of availability in the mode transitions, and has the potential of integration with other models (e.g. mode-based heat transfer models, evaporator models, and chiller or desalination system models).